Evaluating Science Curriculum for the Second Grade from the Perspective of their Teachers - Al-Deeri, Tahani A. (Dirasat: Educational Sciences, 2023)
Objectives: This research aims to evaluate the science curriculum from the perspective of second-grade teachers. Methods: The research used the descriptive and analytical approach as the research nature dictates. The research sample consisted of (100) female teachers from the public schools affiliated with Sahab and Zarqa for the academic year (2021-2022). A questionnaire that contained 104 aspects was conducted and it dealt with six scopes: educational objectives, educational stages objectives, school materials and vocabulary, school book contents, other supplementary activities, information technology, and communication and teaching methods. Results: The research results revealed that the field of supplementary activities ranked first with an arithmetic mean and a standard deviation of (30.57±4.78), while the field of teaching methods came in second place with an arithmetic mean of (30.50±3.96), and the last rank went to the field of subjects’ objectives and vocabulary with an arithmetic mean of (21.12±1.08), the arithmetic mean of the estimates of the research sample on evaluating the science curriculum for the second grade total was (27.89±3.83). The results of the research also showed that there were no statistically significant differences at the level of (a=0.05) between the average estimates of the research sample in the fields of study due to the variable of experience. Conclusions: The research suggests diversifying science curriculum activities to accommodate individual differences and student attitudes. Additionally, it recommends incorporating the concept of the knowledge economy and applying its principles in the curriculum.